Potenciais cognitivos evocados durante a codificação de itens distintos e relacionados entre si: efeitos sobre a recordação livre - Ruiz, Ana Maria Nogueira [UNIFESP] (2006)
Rationale: In free-recall tasks there is a facilitation in recall of semantically related words inserted in the middle serial positions of lists of words with no other relations between them. This facilitation can be due to a series of undetermined cognitive processes such as: a) distinctiveness of the related items; b) activation of preexistent representations in memory; c) processes involved in the integration of related items. The present study sought to investigate the involvement of these processes in the facilitation effect employing both behavioural data and event related potential (ERP) alterations during encoding of words. Methods: Twenty-three undergraduates studied 80 fifteen-word lists in 4 sessions (20 random lists per session). The words in the lists were unrelated except for those in serial positions 7, 8, e 9 de 60 lists, resulting in 4 list types (20 of each) with: a) semantic relations (e.g. milk, cheese, butter); b) phonetic relations (e.g. sea, fee, knee); c) perceptual relations (words related by the type font); d) no relations (control lists). Free-recall was obtained after presentation of each list. ERPs were registered from Fz, Cz and Pz during encoding of words in positions 7, 8, 9 and 10. Results: Recall facilitation varied between lists (semantic> phonetic> perceptual > control). ERPs showed modulations of components identified as P300, N400 and another late positive component (LPC) that varied according to type of relation and electrode location. Among perceptually related words, only that in the 7th serial position was more recalled than in the control list and it led to a positivity that corresponded to a P300. In the 8th and 9th words in the lists with semantic and phonetic relations the N400 was less negative than in control lists but did nor reflect the recall pattern (semantic > phonetic). An LPC occurred only in the 8th word in the semantic lists at FZ and in the 9th in all electrodes in both lists with semantic and phonetic relations which reflected the recall pattern. Conclusion: Results suggest that semantic facilitation effects can be attributed to different processes that occur together at encoding of related stimuli and that are not only due to P300 changes triggered by distinctiveness. P300 amplitude predicted recall only of single distinct items. When there was an opportunity of grouping two or three items such as in the semantic and phonetic lists, N400 and LPC participated in the facilitation effect.